1996
DOI: 10.1074/jbc.271.16.9231
|View full text |Cite
|
Sign up to set email alerts
|

Tβ4 Is Not a Simple G-actin Sequestering Protein and Interacts with F-actin at High Concentration

Abstract: Thymosin ␤ 4 is acknowledged as a major G-actin binding protein maintaining a pool of unassembled actin in motile vertebrate cells. We have examined the function of T␤ 4 in actin assembly in the high range of concentrations (up to 300 M) at which T␤ 4 is found in highly motile blood cells. T␤ 4 behaves as a simple G-actin sequestering protein only in a range of low concentrations (<20 M). As the concentration of T␤ 4 increases, its ability to depolymerize F-actin decreases, due to its interaction with F-actin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 32 publications
4
59
0
1
Order By: Relevance
“…We confirm that the fraction of thymosin ␤ 4 bound to F-actin is insignificant at concentrations up to 30 M (Fig. 1C), in agreement with prior data that implied that if such binding occurred, the K d was several millimolar (10). This observation simplifies the analysis of the anisotropy data, because the anisotropy of labeled thymosin ␤ 4 will therefore only reflect binding to monomeric actin.…”
Section: Validation Of the Anisotropy Assay For Measurement Of Thesupporting
confidence: 91%
See 1 more Smart Citation
“…We confirm that the fraction of thymosin ␤ 4 bound to F-actin is insignificant at concentrations up to 30 M (Fig. 1C), in agreement with prior data that implied that if such binding occurred, the K d was several millimolar (10). This observation simplifies the analysis of the anisotropy data, because the anisotropy of labeled thymosin ␤ 4 will therefore only reflect binding to monomeric actin.…”
Section: Validation Of the Anisotropy Assay For Measurement Of Thesupporting
confidence: 91%
“…Other methods such as the DNase I binding assay yield the sum of A c and an indeterminate fraction of sequestered actin monomer (8). Clever uses of combinations of data have in some cases allowed investigators to subtract F-actin content from total actin and then fractionate the contributions of A c and monomer sequestration (9,10), but the results have proven controversial (11,12).…”
mentioning
confidence: 99%
“…The data obtained from culture cells over-expressing Tb4 demonstrated its binding to F-actin and the promotion of stress fiber formation [Carlier et al, 1996;Sun et al, 1996]. These results suggested that Tb4 sequesters G-actin only at low concentration but binds to F-actin at high concentrations.…”
Section: Structure Of the Actin:thymosin B4 Complexmentioning
confidence: 88%
“…The structural basis of these functional differences between the highly similar repeats is not obvious from their primary structure. Thymosin␤4 can also be cross-linked to F-actin, albeit only at very high concentrations (Carlier et al, 1996). Hence, F-actin-binding by this module is not unprecedented (see also Ballweber et al, 2002).…”
Section: Discussionmentioning
confidence: 99%